Athlete's heart in women. Echocardiographic characterization of highly trained elite female athletes - Pelliccia, A.; Maron, B. J.; Culasso, F.; Spataro, A.; Caselli, G. (Journal of the American Medical Association, 1996)
OBJECTIVES; To define the expression of "athlete's heart" in women by determining the alterations in cardiac dimensions associated with long-term intense conditioning in elite female athletes. DESIGN; Prospective cardiovascular assessment conducted from 1986 through 1993. Subjects were evaluated using 2-dimensional, M-mode, and Doppler echo-cardiographic studies. SETTING: Institute of Sports Science, Italian National Olympic Committee, Rome, Italy. PARTICIPANTS: A total of 600 elite female athletes (mean age, 21 years; range, 12-49 years) who had participated in vigorous training (mean duration, 9 years; range, 2-32 years) and had competed in 27 sports, including 211 athletes at the international level and 389 at the national level. A control group consisted of 65 sedentary volunteer women (mean age, 23.7 years; range, 14-41 years) who were free of cardiovascular disease and who did not participate in regular athletic training. MAIN OUTCOME MEASURES: Left ventricular end-diastolic cavity dimension and wall thickness. RESULTS: Athletes demonstrated larger left ventricular end-diastolic cavity dimension (mean +/- SD) (49 +/- 4 mm) and greater maximal wall thickness (8.2 +/- 0.9 mm) than controls (46 +/- 3 mm and 7.2 +/- 0.6 mm; P < .001). These dimensions were 6% and 14% larger in athletes. Among athletes, left ventricular cavity dimension was 40 mm to 66 mm, exceeded normal limits ( > 54 mm) in 47 women (8%), and was within the range consistent with primary dilated cardiomyopathy ( > or = 60 mm) in 4 athletes (1%). Training for endurance sports, such as cycling, cross-country skiing, and rowing had the greatest effect on cavity dimension. Left ventricular wall thickness was 6 mm to 12 mm in athletes and did not exceed normal limits or extend into the borderline gray zone with hypertrophic cardiomyopathy in any subject. Compared with data from 738 previously studied male athletes, female athletes showed significantly smaller left ventricular cavity dimension (11% less; P < .001) and wall thickness (23% less; P < .001). CONCLUSIONS: Highly trained women athletes frequently demonstrate cardiac dimensional changes as an adaptation to physical training, although absolute left ventricular cavity size exceeding normal limits was evident in a minority (8%) of women athletes and was rarely (1% of athletes) within the range of dilated cardiomyopathy. Athletic training was not a stimulus for substantial increases in absolute left ventricular wall thickness, which was within normal limits for all women athletes. These findings suggest that the clinical differentiation of athlete's heart and hypertrophic cardiomyopathy appears to be a diagnostic dilemma that is limited to male athletes.